Structural, spectroscopic, in silico, in vitro and DNA binding evaluations of tyrosyl-lysyl-threonine - Bicak, Bilge; Kecel Gunduz, Serda; Budama Kilinc, Yasemin; Imhof, Petra; Gok, Bahar; Akman, Gizem; Ozel, Aysen E. (Journal of Biomolecular Structure & Dynamics, 2021)
The main objective of the present study is to investigate the molecular structure and DNA binding interaction of the tyrosyl-lysyl-threonine (YKT) tripeptide, which has anticancer, antioxidant and analgesic properties, using various in silico (MD, QM, molecular docking), spectroscopic (UV, FT-IR, FTIR-ATR, Raman, gel electrophoresis) and in vitro (MCF-7 and HeLa cancer cell lines and BEAS-2B cell line) methods. The optimized geometry, vibrational wavenumbers, molecular electrostatic potential (MEP), natural bond orbital (NBO) and HOMO-LUMO (highest occupied molecular orbital- lowest unoccupied molecular orbital) calculations were carried out with Density Functional Theory (DFT) using B3LYP/6-311++G(d,p) basis set to indicate conformational, vibrational and intramolecular charge transfer characteristics. The assignment of all fundamental theoretical vibration wavenumbers was performed using potential energy distribution analysis (PED). DNA is a significant pharmacological target of drugs in several diseases such as cancer. For this reason, molecular docking calculation was used to elucidate the binding and interaction between YKT tripeptide and DNA at the atomic level. Also, the dynamic behaviors of YKT and DNA was examined using MD simulations. Besides, the interaction of YKT with DNA was experimentally examined by UV titration method and agarose gel electrophoresis method. Experimental results showed that YKT was intercalatively and electrostatically bound to CT-DNA (Calf thymus DNA) and cleavage pBR322 DNA in the presence of H2O2. The pharmacokinetic profile of YKT was also obtained. Cytotoxic effect of YKT was evaluated on MCF-7, HeLa and BEAS-2B cell lines. Hence, these studies about YKT tripeptide may pave the way for the development of various cancer drugs.
CRIS-Team WoS Importer:2021-09-10